The Guide to COIL Virtual Exchange: Implementing, Growing, and Sustaining Collaborative Online International Learning - MARTINS , CAROLINE E.; FERNANDEZ, FRANK (Journal of International Students, 2023)
Virtual Exchange (VE) is a rapidly growing approach to internationalizing the curriculum, offering college students the opportunity to have international experiences without studying abroad. This book contributes new insight to the field of virtual exchange by detailing strategies used for institutionalizing the project-based Collaborative Online International Learning (COIL) VE model, which can greatly enhance the accessibility of internationalization efforts at higher education institutions worldwide. In collaboration with the COIL Connect for Virtual Exchange website, the book showcases perspectives from students, instructors, and institutional leadership, making it a valuable resource for understanding how different stakeholders may benefit from virtual exchange.